Analisis Literasi Keuangan pada Pelaku Usaha Mikro di Kota Pekanbaru - Susie Suryani; Surya Ramadhan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
This study aims to determine the level of financial literacy forMicro, Small and Medium Enterprises in Pekanbaru. Besides that, this research conducted to analyzewhether the differences in gender, age, education level, and income level has significant effect towards financial literacy level for businesses. The focus of business type in this researchis trade sector that contained the number of 292 businesses as sample. The method used is survey by obtaining data through questionnaires. The results showed that the level of SMEss financial literacyis moderate 57,9 percent. variables that affect the level of financial literacy businesses are differences in education and income. While gender and age differences has no effectto the level of MSMEss financial literacy. Keywords : Financial Literation, Gender, Age, Education, Income